2011
DOI: 10.1098/rstb.2010.0117
|View full text |Cite|
|
Sign up to set email alerts
|

Disgust as an adaptive system for disease avoidance behaviour

Abstract: Disgust is an evolved psychological system for protecting organisms from infection through disease avoidant behaviour. This ‘behavioural immune system’, present in a diverse array of species, exhibits universal features that orchestrate hygienic behaviour in response to cues of risk of contact with pathogens. However, disgust is also a dynamic adaptive system. Individuals show variation in pathogen avoidance associated with psychological traits like having a neurotic personality, as well as a consequence of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
342
3
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 603 publications
(361 citation statements)
references
References 91 publications
(123 reference statements)
13
342
3
3
Order By: Relevance
“…(a) Underlying mechanisms Most discussions of the human behavioural immune system assume that the psychological mechanisms that define it are likely to have been adaptive throughout long stretches of human evolutionary history [4,19,33]. This assumption does not, however, imply that each mechanism is an adaptation specific to selection pressures posed solely by infectious diseases.…”
Section: Questions Speculations and Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Underlying mechanisms Most discussions of the human behavioural immune system assume that the psychological mechanisms that define it are likely to have been adaptive throughout long stretches of human evolutionary history [4,19,33]. This assumption does not, however, imply that each mechanism is an adaptation specific to selection pressures posed solely by infectious diseases.…”
Section: Questions Speculations and Directions For Future Researchmentioning
confidence: 99%
“…Much of this work has focused on one specific emotion-disgust-that is associated with diseaseavoidance behaviour, on the specific kinds of perceptual things that elicit disgust, and on the specific circumstances under which a disgust response is either exaggerated or reduced [2,16,17]. This work has been reviewed extensively elsewhere [18,19]. My focus here is on a set of complementary programmes of research that focus less on emotion and more on social cognition and social interaction-lines of enquiry that explore how the behavioural immune system guides people's perceptions of, thoughts about and behaviour towards other individuals within their immediate social ecologies.…”
Section: Introductionmentioning
confidence: 99%
“…Apostolou (2008) similarly showed that both men and women rank health as the fourth most important trait (of 18) in a marriage partner and that men and women rank health as the third most important trait (again, of 18) in a partner for their sons and daughters. The human tendency to avoid disease has since been linked to a host of emotional and behavioral characteristics, including disgust (e.g., Curtis, de Barra, & Aunger, 2011), ethnocentrism (Navarrete & Fessler, 2006, and prejudice and avoidance of those who are physically disabled (Park, Faulkner, & Schaller, 2003).…”
Section: Mate Selection and Healthmentioning
confidence: 99%
“…Sometime in our evolution towards human ultrasociality, disgust took on an extended role-providing a motive to punish antisocial behaviour and to shun the breakers of social rules [8,9]. Disgust is an adaptive system whereby individual responses vary according to an individual's personality and learning experience, as well as by local cultural effects such as norms about manners and the symbolism of pollution and purity [7]. This new synthesis replaces previous conceptions of disgust as, for example, a Freudian means of repudiating desired objects, such as the mother's breast or faeces [10], a psychodynamic balancing mechanism to refuse reminders of our animal nature [6,11,12] or as a social and cultural construction [13,14].…”
Section: Introductionmentioning
confidence: 99%